Chemical Pesticides: Mode of Action and Toxicology - Stenersen, Jorgen (CRC Press, 2009)
Environmental-friendliness, issues of public health, and the pros and cons of genetically-modified crops all receive regular coverage in the world's media. This, in turn, has led to increased questioning and investigation of chemical pesticides. Stenersen's concise and timely introduction to chemical pesticides describes these compounds according to their mode of action at the cellular and biochemical level.